Food-related Adverse Reactions: Alergi dan Intoleransi Makanan - Sheldy Prawibowo (Yayasan Pendidikan Medika Indonesia, 2021)
Food-related adverse reactions can be in the form of food allergies that are mediated by immunity and food intolerance which is mediated by non-immunity. Food allergies and intolerances are often misunderstood by health professionals, patients, and the public. Therefore, the aim of this literature review is to critically review data relating to food allergies and food intolerances. Method. This research is a literature review involving 15 literature sources with the keywords used, namely 'food allergy and food intolerance' with the publication year between 2013- 2020. The abstract and full text of the journal are read and examined, then an analysis of the contents contained inthe objective is carried out. research and research results / findings. Result. It is estimated that one fifth of the population believes they have an adverse reaction to food. Food allergies are different from food intolerance. Some food allergies may be life threatening. The most common food allergens are cow's milk, eggs, peanuts, tree nuts, soybeans, shellfish and fish. Allergic reactions vary from urticaria to anaphylaxis and death. Food intolerance affects15-20% of the population which may be due to pharmacological effects of dietary components, noncoeliac gluten sensitivity or damage to digestive system enzymes and transportation. The most helpful diagnostic test for food intolerance is a food elimination diet to achieve symptom improvement followed by a gradual reintroduction of food.